Acute right heart failure: future perspective with the PERKAT RV pulsatile right ventricular support device - Markus W. Ferrari; P. Christian Schulze; Daniel Kretzschmar (Therapeutic Advances in Cardiovascular Disease, 2020)
Acute right heart failure is associated with impaired prognosis in cardiogenic shock. Since most pharmacological therapies are not evaluated for the failing right ventricle, or even contraindicated, there is a need for rapid minimal invasive circulatory right heart support. The PERKAT RV is such a device for acute therapy in congestive heart failure. It reduces the central venous pooling by pumping blood from the inferior vena cava into the pulmonary artery with flow rates of up to 4 litres/min. The device was evaluated in an animal model of acute pulmonary embolism after careful in vitro tests. PERKAT RV increased cardiac output by 59% in sheep suffering from acute right heart failure. We await the first human implantation in the near future. Based on the PERKAT concept, future devolvement will also focus on left heart support.